The Effect of Energy Parameters of Power Sources on the Structure and Properties of Permanent Joints at Manual Arc Welding; Metals; Vol. 14, iss. 7 - Ilyashchenko D. P. Dmitry Pavlovich (2024, 2024)
Title screen